IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK DI DINAS KEPENDUDUDKAN DAN PENCATATAN SIPIL KABUPATEN BOLAANG MANGONDOW - ANGOW, FETRI OLIVIA; KIYAI, BURHANUDDIN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2018)
This research focuses on the problem of implementing public service policies in the Bolaang Mongondow District Population and Civil Registration Office in the manufacture of e-KTP. This research is intended to find out how the implementation of this public service policy has been carried out in the Bolaang Mongondow District Population and Civil Registration Office in the manufacture of e-KTP. And to help the writer understand how the implementation of this public service policy is applied within the scope of regional government, especially the Office of Population and Civil Registration. This research was conducted using qualitative research methods in the Population and Civil Registration Service, the research informants consisted of program implementers (the Local Government of Bolaang Mongondow Regency and Implementing operators) as well as the community obligatory e-KTP. The results showed that the cause of the lack of maximum implementation of public service policies in the Population and Civil Registration Service, especially in the field of e-KTP manufacture, namely facilities and infrastructure in the process of making e-KTP, as well as bad networks. Based on the research findings then; there needs to be a government policy to pay more attention to the needs that are most needed in the Population and Civil Registration Service so that the process of making this e-KTP can run well in accordance with existing procedures. As for the form of good commitment from employees to carry out their duties in subdivision of regional government programs in the field of Population and Civil Registration; there is support from stakeholders and all community components to support the Dinas program to create an orderly society in population administration.Keywords: Policy Implementation, Public Service, Population Administration.